Association between Physical Activity and Mental Health among School Going Adolescents in Dhulikhel: A Cross-sectional Study - Smita KC; Prakash KC; Tenzing Norbu Lama (Med Phoenix, 2026)
Introduction: Physical activity (PA) is important for both physical and mental health. However, many adolescents face mental health problems due to academic pressure, increased screen time, and lack of physical activity. The aim of the study was to find out the association between of physical activity and the presence of depression, anxiety, and stress among school adolescents in Dhulikhel. Materials and Methods: A cross-sectional study was conducted among 384 students aged 14–19 years from four schools in Dhulikhel using convenience sampling. Physical activity was measured using MVPAQ-A, and mental health was assessed using DASS-Y. Data was analyzed using SPSS version 25. Results: Among 384 adolescents, the mean age was 15.08 ± 1.09 years, with 50.8% females and 49.2% males. Most adolescents had normal mental health status (depression: 80.2%, anxiety: 74.7%, and stress: 83.3%), while 68.2% had moderate physical activity. Physical activity was significantly associated with depression (χ² (6) = 21.813, p=0.001), anxiety (χ²(8)=22.149, p=0.005), and stress (χ²(6)=28.331, p